Peran Akademisi Dalam Memajukan UKM Wajik Tapai Melayu - Sri Maryanti; Nining Sudiar; Afred Suci; Hardi (Universitas Lancang Kuning, 2021)
The purpose of this community service activity scheme for the Regional Superior Product Development Program is to overcome the problem of the Malay tapai partner since 2008, namely the texture of the prouduk that hardens before expiration, the processing process is still conventional and the packaging process is inefficient and ineffective. This greatly affects the efforts of PPPUD partners in advancing their business. The methods used are training, mentoring and activity evaluation. The result of this activity is that the texture of the tapai Malay diamond is softer and more durable using Stabilex BR. The processing process is more efficient because partners use a crystallization evaporator which can save 3 hours with the same quantity of dough. The packaging of tapai malay diamonds has undergone a more contemporary change and shortens the time in the packaging and consumption process in the minds of consumers. This PPPUD activity is very beneficial for partners, it is proven that the problems faced by PPPUD partners can be resolved properly, this is the important role of academics in advancing SMEs.